2017
DOI: 10.1002/rcr2.235
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine profiles of amyopathic dermatomyositis with interstitial lung diseases treated with mycophenolate

Abstract: A 59‐year‐old Japanese man diagnosed with interstitial lung disease associated with amyopathic dermatomyositis with anti‐melanoma differentiation‐associated gene 5 (MDA‐5) antibodies was treated with intravenous methyl prednisolone (PSL) 1000 mg, oral PSL 1 mg/kg, and oral cyclosporin 200 mg daily. His respiratory condition worsened after treatment with two times of intravenous cyclophosphamide and another steroid pulse therapy as well as PSL and cyclosporin. Addition of mycophenolate mofetil (MMF), 1.5 g dail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 5 publications
0
13
0
Order By: Relevance
“…Also, Osterholzer et al suggested that injury toward alveolar epithelial cell could induce inflammatory response resulting in the enrichment of Ly‐6C high monocytes as well . Meanwhile, Hayashi et al identified the decrease of several cytokines after IP‐treatment, including CD87 (augment monocyte adhesion) and MCP‐1 (mediate monocyte chemotactic) . All these evidences emphasized the impact of monocytes on the onset and progress of IP.…”
Section: Discussionmentioning
confidence: 99%
“…Also, Osterholzer et al suggested that injury toward alveolar epithelial cell could induce inflammatory response resulting in the enrichment of Ly‐6C high monocytes as well . Meanwhile, Hayashi et al identified the decrease of several cytokines after IP‐treatment, including CD87 (augment monocyte adhesion) and MCP‐1 (mediate monocyte chemotactic) . All these evidences emphasized the impact of monocytes on the onset and progress of IP.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with ILD and anti-MDA5 antibodies are at a higher risk of pneumocystis carinii pneumonia and prophylaxis should considered for these patients [61]. When the use of calcineurin inhibitors is not feasible, Mycophenolate Mofetil and Rituximab have been used, albeit unsuccessfully in some case reports [87,88].…”
Section: Treatmentmentioning
confidence: 99%
“… 63 Notably, in ADM patients who have antibodies against CADM-140/MDA5 (clinically amyopathic dermatomyositis-140/melanoma differentiation-associated gene 5), serum FKN levels and the anti-CADM-1/MDA5 antibody titer not only correlated with each other but also both correlated with disease activity. 49 , 50 Takada et al also reported that the anti-CADM-140/MDA5 antibody titer can predict the course of rapidly progressing ADM-related ILD. 50 …”
Section: Fkn–cx3cr1 Axis Involvement In the Pathogenesis Of Rheumaticmentioning
confidence: 99%
“…Interstitial lung disease (ILD) is a common extraarticular complication of RA that worsens the prognosis and increases mortality in refractory cases. 46 The role of FKN in the pathogenesis of ILD is currently unknown; however, the FKN–CX3CR1 axis has been implicated in lung involvement in patients with systemic sclerosis (SSc) 47 , 48 and amyopathic dermatomyositis (ADM), 49 , 50 suggesting that this mechanism might also be involved in RA-associated ILD. In a bleomycin-induced model of pulmonary fibrosis, mice lacking C x3 cr1 had reduced levels of pulmonary fibrosis, suggesting that FKN contributes to an inflammatory state that exacerbates ILD.…”
Section: Fkn–cx3cr1 Axis Involvement In the Pathogenesis Of Rheumaticmentioning
confidence: 99%